<span><span>Hiya!
Y=−3x+1
</span><span>
2y=−6x+2
The answer is...
</span></span><span>consistent and coincident
</span>
Hope This Helps!
(If it Helps I took the test, its 100% Right)
(Brainliest is always appreciated)
If You Have Any More Questions Feel Free To Ask! :)
=7(∛2x) - 6(∛2x) - 6(<span>∛x)
= </span>∛2x - 6<span>∛x
answer
C. </span>∛2x - 6∛x
third choice
The answer here is C.
Explanation:
24 feet / 10 inches = 28.8
Then take 60 feet and divide 28.8 by it:
2.08 feet
Then convert 2.08 ft to inches: 24.96 inches
8, 9 you basically just evaluate the equation in the parentheses